Censoring Racial Ridicule : Irish, Jewish, and African American Struggles over Race and Representation, 1890-1930 - Kibler, M. Alison (Book collections on Project MUSE., 2015)
A drunken Irish maid slips and falls. A greedy Jewish pawnbroker lures his female employee into prostitution. An African American man leers at a white woman. These and other, similar images appeared widely on stages and screens across America during the early twentieth century. In this provocative study, M. Alison Kibler uncovers, for the first time, powerful and concurrent campaigns by Irish, Jewish and African Americans against racial ridicule in popular culture at the turn of the twentieth century. Censoring Racial Ridicule explores how Irish, Jewish, and African American groups of the era resisted harmful representations in popular culture by lobbying behind the scenes, boycotting particular acts, and staging theater riots. Kibler demonstrates that these groups' tactics evolved and diverged over time, with some continuing to pursue street protest while others sought redress through new censorship laws.